Synthesis of 4,6-Dimethylpyrimidine 2-Thiosubstituted Derivatives and Their Preliminary Biological Evaluation - Yengoyan, Aleksandr P.; Hambardzumyan, Elen N.; Vorskanyan, Asya S.; Shahbazyan, Lusya V. (Letters in Organic Chemistry, 2021)
Based on 4,6-dimethylpyrimidine-2-thiol hydrochloride a series of its novel S-substituted derivatives including bi- and tricyclic heterosystems with a combination of azines and pyrazole cycles in the molecule were synthesized. The preliminary biological screening has shown that the obtained compounds have a pronounced plants growth-stimulating activity, which is a new property for these heterosystems. This fact indicates the prospectivity of further development of synthesized systems for the search for new plants growth stimulators.
Keywords: 6-dimethylpyrimidine-2-thiol